2014
DOI: 10.1186/bf03353217
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated radar observations of atmospheric diurnal tides in equatorial regions

Abstract: The long-term behavior of atmospheric tides in the mesosphere and lower thermosphere has been observed with the meteor wind radar (MWR) in Jakarta, Indonesia (6• S, 107• E) from November 1992 to August 1997. The amplitudes and phases of the diurnal tides show systematic seasonal variations, particularly distinct in the meridional component. In addition, substantial interannual variability is evident, characterized by a biennial periodicity of tidal parameters, and considerably small tidal amplitudes exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 24 publications
2
39
0
1
Order By: Relevance
“…It is interesting to note that other ground-based studies have also observed tidal phase which increases with height at heights near 80 km (e.g. Tsuda et al, 1999;Buriti et al, 2008;Vincent et al, 1998). Considering the meridional wavelengths presented in Table 1, it can be seen that both observations and eCMAM indicate vertical wavelengths to be between 17 and 30 km for all months.…”
Section: Phases Of the Diurnal Tidementioning
confidence: 92%
See 1 more Smart Citation
“…It is interesting to note that other ground-based studies have also observed tidal phase which increases with height at heights near 80 km (e.g. Tsuda et al, 1999;Buriti et al, 2008;Vincent et al, 1998). Considering the meridional wavelengths presented in Table 1, it can be seen that both observations and eCMAM indicate vertical wavelengths to be between 17 and 30 km for all months.…”
Section: Phases Of the Diurnal Tidementioning
confidence: 92%
“…The results from this location are particularly interesting because it is at a similar latitude to Ascension Island but displaced by approximately 22 • westwards. Tsuda et al (1999) compared diurnal tide radar results between three equatorial sites and found good agreement between Jakarta (6 • S, 107 • E) and Pontianak (0 • N, 109 • W) but significant discrepancies with Christmas Island (2 • N, 158 • W). Friedman et al (2009) A number of studies have reported strong interannual variability of tidal amplitudes (e.g.…”
Section: R N Davis Et Al: Mesospheric Tides Over Ascension Islandmentioning
confidence: 99%
“…The GSWM02 model values also show that over this latitude the diurnal tidal amplitudes of the meridional wind are larger than that of zonal winds. The observations over other low latitude stations, such as Tirnelveli (8.7 • N) (Gurubaran and Rajaram, 1999) and Christmas Island (2 • N), (Chang and Avery, 1997;Manson et al, 1999;Tsuda et al, 1999), also reported that the amplitude of the meridional diurnal tide is greater than that of zonal diurnal component. The amplitude of meridional winds increases up to 90 km and then decreases during June, April and May.…”
Section: Diurnal Tidesmentioning
confidence: 93%
“…It is also known that they are excited by soCorrespondence to: G. Ramkumar (geetha ramkumar@vssc.gov.in) lar heating of water vapor in the troposphere and ozone in the stratosphere. By realizing the importance of tidal activity, extensive wind observations in the MLT region have been carried out across the globe to explore its structure and dynamics (Tetenbaum et al, 1986;Avery et al, 1989;Manson et al, 1988;Portnyagin et al, 1992;Fraser et al, 1995;Tsuda et al, 1999;Zhang et al, 2004). Extensive studies have been carried out on tidal oscillations in the middle and high latitudes, whereas studies from the low-latitude MLT region are very limited (Reddi et al, 1993;Reddi and Ramkumar, 1997;Chang and Avery, 1997;Gurubaran and Rajaram, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, though tidal amplitudes are considered in the HWM-07 model, their day-to-day variability is not taken into account in the model. Amplitudes of the tides may reach values as high as 20 m s −1 over equatorial latitudes (Tsuda et al, 1999). As already mentioned, we have included day-to-day variability of tidal amplitudes into temperature and winds.…”
Section: Application Of Reverse Ray Tracing For the Wave Eventsmentioning
confidence: 99%